Plaque Forming Cell Technique for Counting IgG and IgM antibody-secreting cells in peripheral blood of patients with rheumatoid arthritis - Ayaid Khadem Zgair (World Journal of Experimental Biosciences, 2013)
Antibody Secreting cells are playing a central role in pathogenesis of several autoimmune diseases especially in rheumatoid arthritis. There are few reports describe a method can estimate the number of antibody secreting cells in vitro spontaneously. Here were modified the classical method of plaque forming assay to study the number of IgG and IgM secreting cells [Plaque forming cells (PFCs)] without external stimulators in vitro in peripheral blood of patients with rheumatoid arthritis. Moreover, the relationship between the IgG and IgM concentrations and number of PFC-IgG and IgM (without external stimulators) was studied. The significant increase of IgG as well as IgM antibody secreting cells [plaque forming cell (PFC) - IgG and IgM) was seen in peripheral blood of patients with rheumatoid arthritis (P
Keywords: B-lymphocytes; Plaque Forming cells; Spontaneous activation, modification method